Nature and Extent of ICT Usage in Educational Institutes: An Empirical Study - Sahi , Anu (Gyan Management Journal, 2017)
The objective of this paper was to examine the faculty preferences towards various JCT tools in educational institutes of Northern India comprising majorly the state of Punjab. It specifically aimed to explore the nature and extent of usage of JCT along with factors influencing the usage of JCT among teachers and measuring the impact of usage of JCT on teaching. Primary data had been collected from two hundred teachers of Punjab through the use of a well-structured questionnaire. Data collected had been analyzed through percentages and cross tabulation, AN OVA, and independent sample t- test and Factor analysis has also been used meticulously. The results of the study indicated that teachers in the study found to be fairly using JCT. Teachers have been quite comfortable with usage of computers and their major preferences for JCT tools include multimedia computers, projectors, and MS-office. The teachers surveyed were majorly using JCT for administrative purposes or for preparation of resource materials. Though majority teachers were comfortable with usage of various software's and other JCT tools, yet all of them agree to one thing, that JCT helped them to reduce workload only in terms of administrative work, but has not proved to be rewarding in academic tasks and related rewards like salary increase or promotion. This puts a question mark on the usage of JCT as, if processes have been made easier with JCT, the resulting productivity should be rewarded.
Keywords: iCT,; Educational Institutes; Computers; Softwares; Northern India; Punjab